Analisis Pengaruh Harga, Kualitas, dan Label Halal, Terhadap Minat Beli Mahasiswa Kosmetik Lokal - Muhammad Maulana Arif Ritonga; Nurizal Ismail; Solahuddin Al-Ayyubi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to analyze the influence of price, quality and halal label variables on consumer purchasing interest in local cosmetics. The research method applied was quantitative, where questionnaires were distributed to 107 Muslim students from various universities in Indonesia using a purposive sampling technique. Data was collected via Google Forms and analyzed using SEM-PLS. The research results found that the price variable had an insignificant influence on buying interest. Meanwhile, the quality variable and halal label partially have a positive and significant influence on purchasing interest. Simultaneously all variables have an influence of 74% on buying interest.